KARAKTERISTIK PROSES PENGOLAHAN BANDENG (Chanos chanos) PRESTO SKALA UMKM DI KECAMATAN JUWANA, KABUPATEN PATI - Handoko, Yudi Prasetyo; Apriani, Dita Ambar Kartika; Amrizal, Sri Novalina (Marinade, 2022)
Milkfish has a complex nutritional content, ranging from protein, calcium, fat to vitamins and omega 3. Pati Regency is one of the largest milkfish producers in Central Java Province with one well known product is pressurized milkfish. The purpose of this research was to determine the process flow, to determine the quality of raw materials and products, to calculate the yield, to know the temperature used at each stage of the process, to find out the application of sanitation and hygiene, and to analyze financial aspects. The research method used is descriptive, the data obtained in a clear and detailed anner, and comparatively by comparing the data obtained with references. Pressurizedd milkfish processing consisted of 9 stages from receiving raw materials to packaging. The organoleptic value of raw materials and products was 8. The yield of the removing head and guts process was 92.60% and the cooking process was 43.51%. The application of cold temperatures during the production process has not been carried out properly and correctly. Sanitation and hygiene have not been implemented properly. Simple analizing of the financial aspect for one month of production gained profit of Rp. 43,744,000 with profit margin of 9.35%.